Testing delay of gratification in rats using a within‐session increasing‐delay task. Issue 1 (29th April 2022) - Haynes, Jeremy M.; Odum, Amy L.
Abstract : In delay discounting, preference reversals refer to shifts in preference from a larger‐later reward to a smaller‐sooner reward. Steep hyperbolic discounting predicts a preference reversal when a smaller‐sooner and larger‐later reward both become temporally proximal; prior research is consistent with this prediction. Hyperbolic discounting does not predict a preference reversal, however, after an individual chooses a larger‐later reward over a smaller‐immediate reward; prior research is inconsistent with this prediction. We sought to replicate and extend these findings using a delay of gratification task in rats. The task included a defection response which allowed rats to reverse their preference after choosing a larger‐later sucrose reinforcer to instead obtain a smaller‐immediate sucrose reinforcer. In Experiment 1, we found that rats would defect on their choice of the larger‐later reinforcer, systematically replicating prior research. We also found that experience on the delay of gratification task led to decreases in defection responses. In Experiment 2, we found that prior experience on an intertemporal choice task, with no opportunity to defect, also led to few defection responses on the delay of gratification task. We discuss our findings in the context of whether inhibitory control or temporal learning could be involved in delay of gratification.